Ticari satış sözleşmesi ve ticari satışta ayıp sorumluluğu - Kocar, Serra (My University, 2018)
Satış sözleşmesi; alıcının satılanı devretmeyi, alıcının ise satış bedelini ödemeyi üstlendiği bir akittir. Taraflarının sıfatı ve sözleşmenin amacı dikkate alındığında satış sözleşmesinin adi, ticari ve tüketici anlamda türlere ayrıldığı görülmektedir. Çalışmanın esasını teşkil eden ticari satış sözleşmesinin TTK ve TBK anlamında tanımı yapılmadığından taşıdığı unsurlar dikkate alınarak farklı yorumlamalar yapılmıştır. Öyle ki Borçlar Hukuku anlamında ticari satışta her iki tarafın da tacir olması gerekmemekte, alıcının tekrar satma ve kar sağlama amacına sahip olması yeterlidir. TTK anlamında ticari satışın sınırları ise ticari iş ve TTK m.23/ f.1-c’ye göre belirlenecektir. Ticari satışın sınırlarını çizmek adına tüketici satışı ile ayrımının doğru bir biçimde yapılması gerekmektedir. Bu sebeple TTK m.19/ f.2’ün göre taraflardan yalnız biri için ticari iş niteliğinde olan sözleşmeler Kanunda aksine hüküm bulunmadıkça, diğeri için de ticari iş sayılır. Ancak taraflardan birinin tüketici olması halinde satış tüketici satışı olacaktır. Ayrıca TTK m.19/ f.1’e göre gerçek kişi tacirin ticari iş karinesini çürüterek satış sözleşmesinde tüketici sıfatını kazanabildiği düzenlenmiştir. Ancak tüzel kişi tacirin tüketici sıfatı konusunda görüş farklılığı bulunmaktadır. Tüzel kişi tacirin adi iş sahası bulunmadığından yaptığı bütün satışlar ticaridir.Ticari satışta ayıp sorumluluğu TBK m.219 vd. hükümlerine ve TTK m.23/ f.1-c’ye göre belirlenecektir. TTK m.23/ f.1-c ile adi satışlardaki inceleme ve ihbar külfeti ticari hayata uyarlanmıştır. Zira ticari hayatın hızlı akışı bunu gerekli kılmaktadır. Adi satışlarda alıcı satılandaki ayıbı uygun süre içinde inceleme ve ihbar külfeti altındadır. Ticari satışlarda ise açık veya olağan inceleme ile ortaya çıkacak ayıplar için iki ve sekiz günlük inceleme ve ihbar süresi öngörülmüştür. Burada tacir satıcının ticari faaliyetinin hızlı devam etmesi ve gerekli önlemleri alabilmesi amaçlanmıştır. Söz konusu külfetler yerine getirildikten sonra alıcının TBK m.227 gereği sözleşmede dönme, bedel indirimi, onarım, değişim ve tazminat isteme hakları bulunmaktadır. Alıcı bu hakları 6762 sayılı TTK m.25/ f.4’de öngörülen altı aylık zamanaşımı süresi 6102 sayılı TTK kapsamına alınmadığından TBK m.231 gereği iki yıl içinde kullanmalıdır.

Contract of sale is an agreement in which the seller hands over the sold and the buyer undertakes to pay the sale price. Taking into account of the title of the parties and the purpose of the contract, it is seen that there are three types of the contract of sale: simple, commercial, and consumer. Since the commercial sales contract constituting the basis of the study is not defined in the sense of TCC (Turkish Commercial Code) and TCO (Turkish Code of Obligations), different interpretations have been made considering the components it has. In fact, it is not necessary for both sides to become a trader in the sense of the law of obligations in the commercial sale, and it is sufficient for the buyer to have the purpose of reselling and profit making. The limits of commercial sale in the sense of TCC shall be determined according to commercial business and article 23 / f.1-c of TCC. In order to draw the boundaries of commercial sales, it is necessary to make a proper distinction with consumer sales. For this reason, according to article 19/ f.2 of TCC, contracts, which are a commercial business for only one of the parties, are deemed to be a commercial business for the other, unless otherwise provided in the Code. However, if one of the parties is a consumer, the sale will be consumer sales. In addition, according to article 19 / f. 1 of TCC, it is regulated that the real person trader can acquire the title of the consumer by confuting the commercial business presumption. However, there is a difference of opinion about the consumer title of the corporate person. Since a corporate person does not have the simple business area, all sales it made are commercial.Liability of deficiency in commercial sales shall be determined according to article 219 ff. provisions of TCO and article 23/ f.1-c of TCC. The inspection and notification burden on simple sales have been adapted to commercial life with article 23/ f.1-c of TCC. The rapid flow of commercial life makes it necessary indeed. The buyer is under the burden of inspection and notification the deficiency on the sold within the appropriate period of time in simple sales. In commercial sales, two and eight days of inspection and notification period are provided for defects to be revealed by an open or usual inspection. It is aimed here that the trader seller to continue his/ her commercial activity and to take necessary precautions. After fulfillment of the aforesaid burdens, the buyer has the right to renege on the contract, to reduce the price, to repair, to change and to claim compensation according to article 227 of TCO. Buyer should use these rights within two years pursuant to the article 231 of TCO as the six-month time limit stipulated in article 25/ f.4 of TCC No.6762 is not included in the scope of TCC 6102.
Keywords: ayıp sorumluluğu; commercial sales contracts; Contracts; Economic aspects; Ekonomik yönleri; Franchises (Retail trade); Inspection and Test; inceleme ve ihbar külfeti; liability for defects; Satış hakları (Perakende ticaret); Sözleşmeler; ticari satış sözleşmesi; Turkey; Türkiye